2001
DOI: 10.1002/app.10068
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal crystallization behavior and properties of polypropylene/EPR blends nucleated with sodium benzoate

Abstract: ABSTRACT:The effect of sodium benzoate on the isothermal crystallization behavior of isotactic polypropylene (iPP)/ethylene-propylene rubber(EPR) blends was investigated using differential scanning calorimetry. Dynamic mechanical and physical properties of the iPP/EPR blends nucleated with sodium benzoate were also measured. It was found that the crystallization behavior and physical properties such as heat deflection temperature (HDT), flexural modulus, and impact strength were strongly affected by the compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The integer values of n will depend on the nucleation mechanism, homogeneous or heterogeneous, and on the type of crystal growth, one‐dimensional (rods), two‐dimensional (discs), or three‐dimensional (spheres). The rate constant k is related with the crystal growth and nucleation rates …”
Section: Methodsmentioning
confidence: 99%
“…The integer values of n will depend on the nucleation mechanism, homogeneous or heterogeneous, and on the type of crystal growth, one‐dimensional (rods), two‐dimensional (discs), or three‐dimensional (spheres). The rate constant k is related with the crystal growth and nucleation rates …”
Section: Methodsmentioning
confidence: 99%
“…The differential scanning calorimetric (DSC) analysis of polypropylene (PP)/ acrylonitrile butadiene rubber or nitrile rubber (NBR) blends carried out [6] by George et al reports the influence of NBR on PP crystallinity. Similarly several reports reveal the crystallization behavior of various crystalline/amorphous poly blends [7][8][9][10][11][12][13][14][15][16][17]. Dutt and Kit [7] studied the effect of crystallization conditions on spherulitic texture and tensile properties of syndiotactic polystyrene (PS)/polypropylene oxide (PPO) blends.…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour has been found in iPP blends with other polymers in the crystalline state such as, for example, nylon 6 [38] or in the nematic phase such as Vectra [39]. It has also been observed in iPP blends with other elastomers such as EPR, although in this case the nucleation was related to partial compatibility between components [32,40]. In a very recent study [18], DSC results showed that the presence of SBS and SEBS had a nucleating effect causing an increase in the crystallization temperature of iPP, in agreement with our results.…”
Section: Resultsmentioning
confidence: 77%
“…An organic phosphate derivative has been found to have a very high nucleating efficiency achieved even at very low concentrations which provoked an important increase in the flexural modulus [27,31]. In this regard, the use of a nucleating agent as a third component in the isotactic polypropylene/elastomer blends appears to be a promising alternative to achieve a good balance of properties, although only very few studies have appeared [32,33].…”
Section: Introductionmentioning
confidence: 99%